Improving Students' Physical Literacy Through an Active Learning Approach in Elementary Schools - Hein Wainggai, Heppy; W Mangolo, Ewendi; Qomarrullah, Rifiy (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
Improving physical literacy among elementary school students is a key focus in shaping an active and healthy generation. Physical literacy encompasses the understanding, skills, and motivation to participate in physical activity throughout life. In the context of elementary education, active learning approaches are considered effective for enhancing physical literacy, as this method encourages more dynamic student engagement in the learning process. This study focuses on elementary school students and how active learning approaches are implemented to improve their physical literacy. The aim of this research is to evaluate the effectiveness of active learning approaches in enhancing physical literacy among elementary school students. This study employs a quantitative method with a quasi-experimental approach. The sample consists of 120 students divided into experimental and control groups. Data were collected through physical literacy tests and observations of student activities during the learning process. The findings indicate that students participating in active learning showed significant improvement in physical literacy compared to the control group. This improvement was evident in motor skills, understanding of physical activity concepts, and student motivation to engage in physical activities. The active learning approach proves effective in enhancing physical literacy among elementary school students. Recommendations are provided for educators to integrate this approach into physical education curricula to improve learning quality and encourage active student participation.